Effects of Vitamin D2 and 25-Hydroxyvitamin D2 Supplementation on Plasma Vitamin D Epimeric Metabolites in Adult Cats - Ruggiero, Catherine E.; Backus, Robert C. (Frontiers in Veterinary Science, 2021)
Feline vitamin D status is based on dietary consumption but metabolism of this essential nutrient and the efficacy of supplementation forms are poorly described in cats. The aim of this study was to further elucidate the metabolites of vitamin D2 in cats and to compare the effectiveness of vitamin D2 and 25(OH)D2 for increasing feline vitamin D status. Eight adult male castrated domestic shorthair cats received vitamin D2 or 25(OH)D2 in a single crossover design. Vitamin D2 was dosed daily in a molar equivalent dosage to vitamin D3 ingested in the diet while 25(OH)D2 was provided at a daily dose of 20% molar equivalent intake of dietary vitamin D3 based on its expected higher potency. Plasma concentrations of 25-hydroxyvitamin D epimers were evaluated and baseline then every two weeks for a total of 10 weeks. Analysis of multiple vitamin D metabolite concentrations was completed at the end of each supplementation period, followed by a washout period preceding the second phase of the crossover trial. Results showed that supplementation with 25(OH)D2 more effectively and rapidly raised circulating 25(OH)D2 levels in cat plasma compared to vitamin D2. Formation of C-3 epimers of 25(OH)D3, 25(OH)D2, and 24,25R(OH)2D3, but not 24,25(OH)D2, were observed in feline plasma. The abundant concentrations of epimeric forms of vitamin D metabolites found in circulation suggest that these metabolites should be considered during vitamin D analyses in cats. Further studies using 25(OH)D and vitamin D2 forms are needed to conclude safety and efficacy of these vitamers for supplementation in this species.